IMPLEMENTASI NILAI-NILAI PENDIDIKAN ANTI KORUPSI DI MADRASAH IBTIDAIYAH MELALUI PEMBELAJARAN AQIDAH AKHLAQ - Mohammad Rofiq; Indah Khoirun Nisa (Universitas Pahlawan Tuanku Tambusai, 2022)
Anti-corruption education should be introduced as early as possible from the age of the children. Educational institutions play an important role in shaping anti-corruption behavior for elementary school-age children. Planting which will eventually grow the child's personality and attitude to be more consistent. Anti-corruption education can be carried out formally or informally. At the formal level, elements of anti-corruption education can be included in the curriculum. The curriculum must include all subjects with anti-corruption, learning, habituation, and exemplary values, and teachers must be able to be role models, provide information about the dangers of corruption, and develop students' habits of anti-corruption behavior. The purpose of this study was to instill the values ??of anti-corruption education in elementary school-age children through learning Aqidah Akhlaq at Madrasah Ibtidaiyah. Efforts that can be made to foster the values ??of anti-corruption education in schools include incorporating them into the school curriculum by integrating them into subjects. The result of the discussion in this study is that through the Aqidah Akhlaq material developed it is able to attract students' interest in learning about the values ??of anti-corruption education. Through this integration, it is able to increase understanding and awareness of the importance of anti-corruption behavior in students at the Madrasah Ibtidaiyah stage Keywords: Anti-Corruption Education, Aqidah Akhlak Subject, Madrasah Ibtidaiyah